Studi Evaluasi Pengelolaan Limbah B3 di Galangan PT. X - Bunga Ervina Rahma Berliana Putri; Muhammad Faisal Fadhil (Jurnal Serambi Engineering, 2025)
The shipyard of PT. X generates a huge amount of hazardous trash from ship repair activities, such as sandblasting waste, spent oil, used paint cans, and cleaning cloths. The purpose of this study is to classify and appraise B3 waste management operations, as well as to evaluate their execution. Data were gathered from observations, measurements, and interviews with the person in charge of Hazardous Waste Storage at the shipyard of PT. X. This study uses four stages in its implementation method, namely data collection, data processing and analysis, withdrawal, and provision of recommendations. Then the data will be compared with the applicable regulations. The average percentage of scoring was 73.375% with the achievement of "GOOD". However, the aspect of B3 waste storage needs to be improved because it got a low score of 56% with the achievement category of "FAIR". The same thing also happened in the aspect of packaging and container of B3 waste which only got a score of 37.5% with the achievement category of "POOR". With low scores for these aspects, it will result in the risk of environmental pollution, endanger the health and safety of workers, and can damage the company's reputation because it has violated existing regulations. Therefore, it is necessary to make improvements to improve the suitability of Hazardous waste management at PT. X based on applicable regulations.